Tetramethylpyrazine Ameliorates Lipopolysaccharide-Induced Sepsis in Rats via Protecting Blood–Brain Barrier, Impairing Inflammation and Nitrous Oxide Systems - Huang, Zi-Sheng; Xie, Da-Qi; Xu, Li-Jun; Huang, Chang-Shun; Zheng, Min; Chen, Yi-Jun; Cao, Yin (Frontiers in Pharmacology, 2020)
The aim of this study was to assess the underlying impact of Tetramethylpyrazine (TMP), which is the main activity compound of Ligusticum chuanxiong Hort, on the blood–brain barrier, inflammatory and nitrous oxide systems in a rat model of lipopolysaccharide (LPS)-induced sepsis. The SD rats were divided into control group, LPS treatment group, and LPS + TMP treatment group. TMP administered by tail vein injection. The mortality of experimental rats was recorded during the experiment. Rats were sacrificed after 14 days. Peripheral blood was collected and the expression levels of inflammatory factors TNF-α, IL-1β, and IL-6 were detected by ELISA. The integrity of blood-brain barrier was detected by sodium fluorescein staining. Lung and brain tissues were taken to detect the infiltration of immune cells. Immunohistochemistry was performed to detect the expression of tight junctions related proteins and oxidative stress-related proteins. The results showed that TMP treatment for 14 days significantly decreased the weight loss and increased the survival rate of the septic rats significantly. TMP decreased the infiltration of inflammatory cells and alleviated the sepsis-induced damage in both the lung and brain tissues. The inflammatory cytokines TNF-α, IL-1β, and IL-6, were significantly decreased post-TMP treatment. Histopathological analysis with sodium fluorescein staining density showed that TMP had a protective effect on the basal lamina and cerebral cortex. Also, TMP significantly increased expression of the tight junction-related proteins claudin-5 and occludin in the brain tissue and increased the expression of the ZO-1, Occludin, and Claudin-5 genes, indicating alleviated the degree of blood–brain barrier destruction. Furthermore, immunohistochemistry (IHC) and immunoblotting confirmed that TMP could inhibit the indicators of the nitrous oxide system, iNOS and eNOS; in addition, TMP significantly decreased the levels of MDA and NO. The findings showed that TMP treatment during sepsis was associated with the protection of the blood–brain barrier and the suppression of inflammatory reactions and the nitrous oxide system. This study reveals a promising protective role of TMP in septic encephalopathy and may suggest a therapeutic approach for fighting the deadly disease of sepsis in the clinic.